Clinical outcome after treatment of single and multiple cartilage defects by autologous matrix-induced chondrogenesis. (30th May 2019) - Gudas, Rimtautas; Mačiulaitis, Justinas; Staškūnas, Mantas; Smailys, Alfredas
Purpose: Characterized cartilage lesions have a distinct impact on postoperative clinical outcome, which is still being evaluated. The purpose of this study was to assess the postoperative clinical outcome of autologous matrix-induced chondrogenesis (AMIC) for characterized cartilage lesions. Methods: Fifteen patients with articular cartilage (AC) defects of the knee were included in the study. AC defects were characterized intraoperatively by International Cartilage Repair Society score. Grade III–IV AC lesions were treated with AMIC; grade I–II lesions were left untreated. Patients were divided into subgroups and clinically evaluated by subjective autologous matrix-induced chondrogenesis (IKDC) and Tegner scores at median follow-up of 4.5 years. Results: Twenty-eight AC defects were diagnosed (1.9/patient). Multiple subgroup had larger diagnosed (7 ± 2.3 cm 2, p = 0.022) and untreated (3.1 ± 2.3 cm 2, p = 0.012) lesion areas than the single subgroup. Partly treated subgroup had larger untreated defect areas (3.6±2.3 cm 2, p = 0.025) than the Treated subgroup. Average subjective IKDC values of total group and individual subgroups improved significantly at follow-up. More patients restored their previous activity levels ( p = 0.026) and had higher incremental subjective IKDC scores ( p = 0.014) in the single subgroup than the multiple subgroup. Diagnosed defect size negatively correlated to subjective IKDC incremental ( r = −0.624, p = 0.023) and postoperative scores ( r = −0.545, p = 0.054) in total group. Conclusions: AMIC can have a clinically relevant outcome for patients with single or multiple knee AC lesions; however, clinical outcome is superior in patients with a single defect per knee. Patients with single defects returned to previous physical activity levels significantly faster than patients with multiple defects. Diagnosed AC defect areas negatively correlate to clinical improvement at follow-up.